A diversified dinosaur track assemblage from the Lower Cretaceous Xiaoba Formation of Sichuan Province, China: Implications for ichnological database and census studies. (April 2019) - Xing, Lida; Lockley, Martin G.; Tong, Kui; Peng, Guangzhao; Romilio, Anthony; Klein, Hendrik; Persons, W. Scott; Ye, Yong; Jiang, Shan
Abstract: The rapid rate of discovery of Lower Cretaceous tetrapod tracksites in terrestrial sequences on the Sichuan Basin area is such that the 2016 report of 21 sites in the Xiaoba, Feitianshan and Jiaguan Formations is now increased by ∼24%–26 sites. Of these seven occur in the Xiaoba Formation, including two new sites (Luogan and Apuruha) described here. Likewise, there has been a similar increase in reports of sites from the Jiaguan Formation, from 12 to 15 sites (=25%) in the same period. The total of estimated trackmakers, based on trackways, not individual tracks, is ∼598 for all three formations, including∼150 from the Xiaoba Formation, and ∼325 from the Jiaguan Formation. This indicates a two-year increase in the database of ∼20%. To date all tracks from the Xiaoba formation represent saurischians (non-avian theropods and sauropods). However, as the database has increased for all three formations it has been possible to demonstrate that didactyl, presumably deinonychosaurian trackmakers, although rare and in some cases poorly preserved, occur in about 20% of assemblages. Thus, the data base helps differentiate between the relatively low abundance and relatively widespread distribution of deinonychosaurian trackmakers within the non-avian theropod track database. This difference between abundance and distribution is consistent with what is known of patterns in other parts of Asia.